2012
DOI: 10.1167/iovs.12-10037
|View full text |Cite
|
Sign up to set email alerts
|

Transcorneal Electrical Stimulation Shows Neuroprotective Effects in Retinas of Light-Exposed Rats

Abstract: PURPOSE.To examine the effects of transcorneal electrical stimulation (TES) on retinal degeneration of light-exposed rats.METHODS. Thirty-three Sprague Dawley albino rats were divided into three groups: STIM (n ¼ 15) received 60 minutes of TES, whereas SHAM (n ¼ 15) received identical sham stimulation 2 hours before exposure to bright light with 16,000 lux; healthy animals (n ¼ 3) served as controls for histology. At baseline and weekly for 3 consecutive weeks, dark-and light-adapted electroretinography was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 59 publications
1
29
0
5
Order By: Relevance
“…However, beneficial effects of ES have been shown in one study using transorbital ES 14 and in several animal experiments using TES (Table 1). 15e35 These studies can be categorized as follows: i) healthy animals 17e19, 23,26,31,34 ; ii) transgenic animals 22,28 ; iii) animals as a disease model for RP 21 ; iv) animals with induced ischemic insult, 27,29,33 optic nerve crush, 15,16,20,32 and transected optic nerve 24,25 ; and v) animal cells isolated from the retina. 35 …”
Section: Animal Experimentsmentioning
confidence: 99%
“…However, beneficial effects of ES have been shown in one study using transorbital ES 14 and in several animal experiments using TES (Table 1). 15e35 These studies can be categorized as follows: i) healthy animals 17e19, 23,26,31,34 ; ii) transgenic animals 22,28 ; iii) animals as a disease model for RP 21 ; iv) animals with induced ischemic insult, 27,29,33 optic nerve crush, 15,16,20,32 and transected optic nerve 24,25 ; and v) animal cells isolated from the retina. 35 …”
Section: Animal Experimentsmentioning
confidence: 99%
“…The mechanism for these positive effects has been suggested to be a favorable regulation of neurotropic factors; electrical stimulation has been linked to the upregulation of neurotrophins in the central and peripheral nervous systems [1618], whereas in animal experiments, electrical stimulation has been shown to be beneficial for the survival of photoreceptors in Royal College of Surgeon’s rats [19] promoting the survival of photoreceptors and improving retinal function in rhodopsin P347L transgenic rabbits [20], rescuing ganglion cells after optic nerve injury in Wistar rats [21, 22], and preserving retinal cells after light-induced retinal damage in Sprague–Dawley rats [2325]. …”
Section: Introductionmentioning
confidence: 99%
“…This configuration differs from TES and SES in that the applied electrical field, and thus the currents, are more uniformly distributed through the entire eye. It should be noted that this review will classify some studies identified as TES in the literature as WES due to reference electrode placement away from the cornea [8,9]. Neuroprotective current levels for TES and WES appear in the range of 1.5 to 1000 µA.…”
Section: Types Of Est Applied To the Retinamentioning
confidence: 99%
“…After WES stimulation every 3 days for 14 days with a contact lens electrode referenced to the opposite eye, albino rats exposed to bright light had significantly preserved a-and b-wave amplitudes [16]. EST for 2 h with a DTL fiber on the cornea (location of reference electrode not described) prior to a milder light exposure temporarily preserved b-wave amplitudes and some photoreceptors and rod outer segments after 3 weeks [8]. These effects were not as great as that reported by Ni et al [16], possibly due to the different electrode configuration and the absence of repeated EST sessions.…”
Section: Est Preserves Photoreceptorsmentioning
confidence: 99%